Monomer driven growth of catalytically active AgAu plasmonic nanoalloys. (February 2022) - Newmai, M. Boazbou; Verma, Manoj; Dahiya, Annu; Kumar, Pandian Senthil
Abstract: Ag–Au alloy nanoparticles were effortlessly synthesized with the seed Ag nanoparticles acting as sacrificial template for the effective reduction of Au 3+ ions to Au 0 atoms, augmented in the presence of the monomer, NVP ( N -vinyl pyrrolidone) assimilated in specific solvents. The conventional spherical morphology of the different Ag–Au alloy molar compositions confirmed using TEM corroborates their red-shifted optical absorption spectra along with the strain induced XRD patterns in accordance with Vegard's law. FTIR spectroscopy depicts clearly the solvation property of NVP and also its respective molecular interaction of individual metal and alloy nanostructures. The amine group of NVP despite its possible steric hindrance seems to coordinate well with monometallic Ag nanoparticles; while for bimetallic Ag–Au nanoparticles, the combined amine and carbonyl groups plays a major role in stabilizing the nanostructure. No evidence of oligomerization/polymerization is observed even after the formation of respective nanoparticles, representing the intriguing configuration of the monomer NVP, the behavior of which seems equivalent to that of its long chain polymer counterpart, PVP. The catalytic properties of the as-synthesized Ag–Au alloy nanoparticles were carefully analyzed in comparison with other polymer/surfactant coated alloy nanoparticles and their significance is established in a cohesive manner. Graphical abstract: Image 1 Highlights: AgAu plasmonic nanoalloys synthesized using monomer NVP ( N -vinyl pyrrolidone) assimilated in specific solvents. Formation mechanism delineated using FTIR spectroscopy. Molecular interaction of NVP with individual metal and alloy nanostructures is discussed in detail. Catalytic activity of plasmonic nanoalloys were established.